Implikasi Konsep Yesus Pengudus Menurut A.B. Simpson Bagi Orang Kristen Masa Kini - Ayu Rotama Silitonga; Priskha Natonis; I Putu Ayub Darmawan (Sekolah Tinggi Teologi Bethel Ambon, 2020)
Sanctification is a blessing and gift from God to believers. According to Albert Benyamin Simpson, the Holy Jesus has an important meaning, which is a form of complete submission to God. The problem formulation in this writing is what is the concept of Jesus the Holiness according to the thought of Albert Benjamin Simpson? The purpose of this paper is to know the concept of the Holy Jesus according to the thought of Albert Benyamin Simpson. To obtain information in this writing, the writer uses the Literature method by observing books and journals to support writing. The result of this writing is that Simpson thinks that the concept of Jesus is a form of submission to God. The meaning of the Holy Jesus as explained by the author is to live in holiness and as a sign of submission to God. The implication that today's believers can do is continue to believe in God and fully surrender to the Lord Jesus Christ as a sanctuary. Abstrak:Pengudusan merupakan berkat dan anugrah dari Tuhan kepada orang percaya. Menurut Albert Benyamin Simpson, Yesus Pengudus memiliki makna penting, yaitu bentuk penyerahan diri sepenuhnya kepada Allah. Yang menjadi rumusan masalah dalam penulisan ini ialah seperti apa konsep Yesus Pengudus menurut pemikiran Albert Benyamin Simpson? Adapun tujuan dalam penulisan ini ialah untuk mengetahui konsep Yesus Pengudus menurut pemikiran Albert Benyamin Simpson. Untuk mendapatkan informasi dalam penulisan ini, maka penulis menggunakan metode Literatur dengan melakukan observasi terhadap buku-buku dan jurnal untuk mendukung penulisan. Hasil dari penulisan ini adalah Simpson beranggapan bahwa konsep Yesus Pengudus ialah bentuk penyerahan diri kepada Allah. Makna Yesus Pengudus yang dipaparkan oleh penulis adalah hidup dalam kekudusan dan sebagai tanda penyerahan diri kepada Allah. Implikasi yang dapat dilakukan orang percaya masa kini adalah tetap percaya kepada Tuhan dan berserah penuh kepada Tuhan Yesus Kristus sebagai pengudus.